2015
DOI: 10.1177/0284185114524198
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of asymptomatic cerebral microbleeds in patients with hemorrhagic onset-type moyamoya disease: a phase-sensitive MRI study and meta-analysis

Abstract: PSI or SWI can detect CMBs better than T2*WI, and 3-T T2*WI. Hemorrhagic onset-type moyamoya disease seems to correlate with a high incidence of asymptomatic CMBs. The meta-analysis indicates that asymptomatic CMBs may be an important factor for hemorrhagic stroke risk. Long-term evaluation of CMBs using PSI or SWI may contribute to the management of moyamoya disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…However, when comparing our data with pooled data from a recent meta-analysis 13 of 5 publications (of Asian/Japanese populations), 7,10,11,13,21 rather than single studies, a different picture emerges. The pooled number of cMBs in these studies was 76 patients (30.8%) in 246.…”
Section: February 2017mentioning
confidence: 68%
See 2 more Smart Citations
“…However, when comparing our data with pooled data from a recent meta-analysis 13 of 5 publications (of Asian/Japanese populations), 7,10,11,13,21 rather than single studies, a different picture emerges. The pooled number of cMBs in these studies was 76 patients (30.8%) in 246.…”
Section: February 2017mentioning
confidence: 68%
“…24 The Rotterdam Scan study reported the agespecific prevalence of cMBs as 5.4% for the age group of 60 to 69 years rising to 23.3% for the age group of 80 to 97 years. 25 Furthermore, the pooled estimate of the proportion of cMBs in the meta-analysis of Qin et al 13 (one of which was an update of the aforementioned Kikuta study 8 ) in Asian moyamoya patients was ≈30%. Our moyamoya collective has significantly less cMB, supporting the alternative hypothesis that they come from substantially different moyamoya populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consistent with the other previous study. 20 Although our study did not investigate subsequent hemorrhages in patients with MMD with microbleeds, several studies have reported the presence of microbleeds as a predictor of subsequent hemorrhagic stroke in patients with MMD. 12,14,23,26 Microbleeds in patients with MMD have mainly been reported in deep brain areas, such as the periventricular white matter, basal ganglia, or thalami, and they mainly occur in arteries displaying the subependymal-leptomeningeal artery anastomosis pattern.…”
Section: Discussionmentioning
confidence: 89%
“…7,[10][11][12]20 Kikuta et al demonstrated a higher prevalence (44%) of cerebral microbleeds in patients with MMD than in healthy individuals (5.8%). 11 Our detection rate (8.1%) of microbleeds is the first reported in Korean patients with MMD and was rela- tively lower than those in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%